Comprehensive Analysis and Comparison on the Codon Usage Pattern of Whole Mycobacterium tuberculosis Coding Genome from Different Area. (8th May 2018) - Gun, Li; Yumiao, Ren; Haixian, Pan; Liang, Zhang
Abstract : Phenomenon of unequal use of synonymous codons in Mycobacterium tuberculosis is common. Codon usage bias not only plays an important regulatory role at the level of gene expression, but also helps in improving the accuracy and efficiency of translation. Meanwhile, codon usage pattern of Mycobacterium tuberculosis genome is important for interpreting evolutionary characteristics in species. In order to investigate the codon usage pattern of the Mycobacterium tuberculosis genome, 12 Mycobacterium tuberculosis genomes from different area are downloaded from the GeneBank. The correlations betweenG 3, G C 12, wholeG C content, codon adaptation index, codon bias index, and so on of Mycobacterium tuberculosis genomes are calculated. The ENC-plot, relationship betweenA 3 / ( A 3 + T 3 ) andG 3 / ( G 3 + C 3 ), G C 12 versusG C 3 plot, and the RSCU of overall/separated genomes all show that the codon usage bias exists in all 12 Mycobacterium tuberculosis genomes. Lastly, relationship between CBI and the equalization of ENC shows a strong negative correlation between them. The relationship between protein length and GC content (G C 3 andG C 12 ) shows that more obvious differences in the GC content may be in shorter protein. These results show that codon usage bias existing in the Mycobacterium tuberculosis genomes could be used for further study on their evolutionary phenomenon.